Mengintegrasikan Prinsip-Prinsip Manajemen Perubahan Perekonomian Dalam Perspektif Islam - Mustafaruddin Mustafaruddin; Nuri Aslami (LPPM Universitas Labuhanbatu, 2026)
Islam is order and harmony. The only teaching in the world that has a system and concept of a perfect arrangement of life. The completeness of these rules is in line with harmony with the characteristics and behavior of humans. Economics is an inseparable part of the concept of Islamic teachings. Islamic economics is inherently a logical consequence of the perfection of Islam itself. Islam must be embraced kaffah and by his people. Islam demands its followers to realize their Islam in all aspects of their lives including the economy.